Penerapan dan Analisis Network Security Snort Menggunakan Intrusion Detection System pada Serangan UDP Flood - Karina Fitriwulandari Ilham Ilham; Erick Irawadi Alwi; Farniwati Fattah (INFORMAL: Informatics Journal, 2023)
The web server is one type of server that was most frequently attacked because the web server is the most vital means for storing databases. The most frequently used attack is Denial of Service (DoS). DoS is an attack technique against a system by consuming data resources from a server so that the server cannot be accessed again. Therefore, this study aims to design a network security system by implementing an Intrusion Detection System (IDS) using the Snort application as a detection system in the event of a DoS attack on the web server. by implementing Snort on a web server will help network administrators to ensure that the web server is protected from various threats. The results of this study indicates that the Snort rule that has been created has been successfully detecting attacks that have been tested through the LOIC tools.